2020
DOI: 10.1186/s12884-020-03214-1
|View full text |Cite
|
Sign up to set email alerts
|

Rare heterotopic pregnancy after frozen embryo transfer: a case report and literature review

Abstract: Background Heterotopic pregnancy occurred after frozen embryo transfer with two D3 embryos, and the case had a history of bilateral salpingectomy due to salpingocyesis. An ectopic heterotopic pregnancy was implanted in the left psoas major muscle, which has not been previously reported. Case presentation A 33-year-old woman presented with left back pain after curettage due to foetal arrest in the uterus without vaginal bleeding and spotting, and painkillers relieved the pain initially. When the painkillers c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
(21 reference statements)
0
13
0
Order By: Relevance
“…The iatrogenic placement of the embryos in the retroperitoneal space of the mid or upper abdomen can definitely be excluded considering the length of the transfer catheter and the volume of the ET medium [ 9 – 11 , 14 ]. Wang et al [ 32 ] speculated that the fallopian tube stumps after resection could be spontaneously reperfused or formed a fistula, creating a possible communication between the uterine and the retroperitoneal cavity. However, in the case reported by Anh et al [ 35 ], both fallopian tube stumps were visible and intact, and detached from the broad ligaments, excluding this explanation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The iatrogenic placement of the embryos in the retroperitoneal space of the mid or upper abdomen can definitely be excluded considering the length of the transfer catheter and the volume of the ET medium [ 9 – 11 , 14 ]. Wang et al [ 32 ] speculated that the fallopian tube stumps after resection could be spontaneously reperfused or formed a fistula, creating a possible communication between the uterine and the retroperitoneal cavity. However, in the case reported by Anh et al [ 35 ], both fallopian tube stumps were visible and intact, and detached from the broad ligaments, excluding this explanation.…”
Section: Discussionmentioning
confidence: 99%
“…And significantly, the region of pain does not fully reflect the implantation site of pregnancy. Only one case, reported by Wang et al [ 32 ], complained of pain in the left lumbar back which might be caused by ectopic gestational sac growth resulting in stimulation of the nerve of the left psoas major muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Methotrexate (MTX) is the most frequently used drug in REP. Jiang et al showed that administration of MTX pre‐operation would reduce intraoperative blood loss for complete mass removal 12 . While, Wang et al reported an REP case successfully treated with surgery and MTX intramuscularly at the gestational sac implanting site after gestational sac removing 16 . Moreover, Huang et al suggested MTX injection in the gestational sac as a safe and effective treatment to REP 17 .…”
Section: Discussionmentioning
confidence: 99%
“…According to this, careful clinical and ultrasound investigations, especially adnexa examination findings, are necessary in asymptomatic patients. Due to the importance of heterotopic pregnancy and its prevalence among the patients using fertility medications and assisted reproduction techniques, such as IVF, the adnexa should be well checked even after detecting a gestational sac containing the yolk sac and observing an embryo in the endometrial cavity to rule out heterotopic pregnancy (3).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery may successfully save most of these types of pregnancies and therefore embryos if the condition is diagnosed early. Careful clinical or ultrasound examination of adnexa in asymptomatic patients is necessary and helpful for achieving an accurate diagnosis and formulating a logical therapeutic plan (3).…”
Section: Introductionmentioning
confidence: 99%